Evaluation of the Spatial Accessibility and MRT Ridership in Dhaka - Esha, Farhana Khatun; Haque, Afsana (The Jahangirnagar Review, 2025)
Accessibility is an essential factor in determining ridership in account of MRT enables individuals with a range of abilities to get involved in society and access opportunities, accessibility is crucial for public transportation, particularly for Mass Rapid Transit (MRT) systems. Analysing five operational metro stations—Motijheel, Bangladesh Secretariat, Shahbagh, Shewrapara, as well as Mirpur 10—this study assesses spatial accessibility and its link to Mass Rapid Transit (MRT) Line 6 ridership in Dhaka. These transit hubs are fully operational elements of the city’s transport system, not only "proposed." To evaluate the effects of road facilities, footpaths availability, intersection density, spatial connectivity, and accessibility to important urban services on commuter behaviour and station-level ridership, the study combines quantitative and qualitative methods. Indicators such as shortest path distances, the quantity and kind of facilities (such as commercial, healthcare, and educational), road width and length, and the existence of footpaths were examined employing ArcMap-based network analysis to create accessibility scores for every station. Motijheel dominated in passenger traffic, however Mirpur 10 did not have the largest ridership, even though it had the highest accessibility ranking based on service count. Shahbagh, on the other hand, earned an inferior accessibility score yet still had a high commuter volume. These discrepancies imply that trip intent, land use context, including modal preferences (like walking) are important factors that influence ridership in addition to accessibility. The results show that in order to increase MRT efficiency and promote inclusive urban mobility, a multifaceted understanding of urban connectivity is required.